Generación de biogás en la avícola las Amelias de la ciudad de Latacunga en el año 2016, a partir del estiércol de gallina. Propuesta de diseño de un biodigestor - Osorio Jiménez, Paúl Hernán (2017)
The present investigation Project is based on the design of a continous flow digestor of the rectangle type under the land surface from the hen manure in Pusuchisí neighborhood, Ignacio Flores Parish, Latacunga, town, Cotopaxi province. The experimental method was applied for the analysis of the biodigestor design parameters of continuos flow through a experimental biodigestor design, which has a polyethylene plastic container with a capability of 20 litres, at the top of the lid, a channel of exit of ½ “ biol was adapted, it is communicated with the fermentation in which a turn around valve of ½” to control the bio-gas exit, moreover it was installed a plastic container (ballon) for the capture, quantification and storage of bio-gas, with a time of retention of 30 days to room temperatura. The results obtained of the experimental biodigestor designs and the quantity of organic matter generated by the poultry was divided for the biodigestor design of rectangle, continous flow, as conclusion 1050 Kg of hen manure was obtained weekly, it represents 13,440 ml of biogas, and the total of organic matter generated in the poultry is 4200 Kg, it means we will get 53,760 ml of bio-gas, therefore it´s necessary a fermentation chamber of 5 meters of long, 1,20 meters of width and 1,50 meters of height for the degradation of the organic matter and the accumulation pocket of bio-gas will be the third part of the volumen. This research guides to the generation of a clean fuel to substitute the fossils so that to use for the warming of the laying hen sheds in order to maintain a temperatura from 12 grades as minimun to 21 grades to maximun, it permits a normal production of eggs in the poultry.